Дослідження мікроелементного складу сировини Duschekia viridis (Chaix) Opiz. - Кулагіна, М. А.; Козира, С. А.; Радько, О. В.; Сербін, А. Г.; Кулагина, М. А.; Козыра, С. А.; Сербин, А. Г.; Kulagina, M. A.; Kozyra, S. A.; Radko, E. V.; Serbin, A. G. (Запорізький державний медичний університет, 2013)
Дослідили мікроелементний склад кори, листків і суплідь Duschekia viridis (Chaix) Opiz. Ідентифікували 11 елементів і визначили їхній кількісний вміст у сировині. Исследован микроэлементный состав коры, листьев и соплодий Duschekia viridis (Chaix) Opiz. Идентифицировали 11 элементов и изучили их количественное содержание в сырье. The microelement compounds of a bark, leaves and collective fruits of Duschekia viridis (Chaix) Opiz. were investigated. 11 elements were identified and their quantities were determined.
Изучение микроэлементного состава сырья Duschekia viridis (Сhaix) Opiz.
Study of microelement composition of Duschekia viridis (Chaix) Opiz. row material
Keywords: Duschekia viridis (Chaix) Opiz.; кора; листя; супліддя; мікроелементний склад; листья; соплодия; микроэлементный состав; bark; leaves; collective fruits; microelement compound